(untitled) (American Journal of Technology and Applied Sciences, 2024)
In this article the authorscarried out a review of the literature on aspects of one of the current and little-studied problems in endocrinology, namely, the problems of premature sexual development. The article covers the issues of etiopathogenesis, classification, clinical picture, diagnosis and treatment of the disease.